2014
DOI: 10.1001/jamasurg.2013.3384
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Grafts in Adult and Pediatric Liver Transplantation

Abstract: Use of segmental allografts is essential to offer timely transplantation and decrease waiting list mortality. Living donor liver transplants and segmental grafts from deceased donors are complementary. It is possible to have excellent outcomes combining a multidisciplinary team approach, technical expertise, routine use of anticoagulation, and strict patient and donor selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 48 publications
0
11
0
1
Order By: Relevance
“…However, for adult candidates, frequency of vascular thromboses and biliary complications has abated such that they now occur in similar rates among recipients of either graft type. (10,20,21) In addition, the study might be subject to confounding by indication as candidates for whom physicians felt comfortable accepting an offer for a split graft might be different from those for whom it was declined. The possibility exists that the favorable outcomes following SLT for small children and adults were the result of careful candidate selection on the part of health care teams.…”
Section: Original Article | 981mentioning
confidence: 99%
“…However, for adult candidates, frequency of vascular thromboses and biliary complications has abated such that they now occur in similar rates among recipients of either graft type. (10,20,21) In addition, the study might be subject to confounding by indication as candidates for whom physicians felt comfortable accepting an offer for a split graft might be different from those for whom it was declined. The possibility exists that the favorable outcomes following SLT for small children and adults were the result of careful candidate selection on the part of health care teams.…”
Section: Original Article | 981mentioning
confidence: 99%
“…22 These challenges associated with LDLT in pediatric patients highlight the need for refining surgical technique training and the importance of close collaboration with infectious disease experts for the prevention of infection-related complications, as well as quality improvement strategies. 6,23,24 Previous studies of adult LT have suggested that SSIs do not significantly affect patient survival but can significantly decrease graft survival. Among pediatric LT recipients, infection in the early postoperative period was associated with significant morbidity but no increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…5 At our center, more than 50% of our pediatric recipients received SG, mainly from living donation. 6 In adult patients, the SSI rate after LDLT is higher than that in deceased donor LT. 3,[7][8][9] SG used in LT pose added difficulty for many reasons, including the presence of a cut surface, which is known to increase the incidence of biliary complications and therefore a potential increased risk of SSIs. 10,11 Other groups have shown that the presence of SSI following LT is associated with increased postoperative morbidity, high costs, and increased resource utilization.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…246 Hepatic artery stenosis (HAS) can be a precursor to HAT, with an incidence in children of 2.8%. 247 It is diagnosed by Doppler ultrasound imaging, and the gold standard is angiography and is best managed by angioplasty and endovascular interventions. 248 Venous complications.…”
Section: Surgical Complications Vascular Complicationsmentioning
confidence: 99%